Peningkatan Pengetahuan dan Keterampilan Dalam Penanganan Pertolongan Pertama Pada Luka Bakar Desa Ledug Purwokerto - Khoirussalim, Moh; Handayani, Rahmaya Nova; Rahmawati, Arni Nur (Yayasan Daarul Huda Kruengmane, 2024)
Burns are a type of tissue damage or loss caused by contact with heat sources such as fire, boiling water, hot oil, electric shockand chemicals. Special treatment or first aid for burns is by removing accessories attached to the skin. Then pour room temperature water on the burned area for 15 minutes or use running water and bandage using a soft cloth or cotton that has been moistened with water. The purpose of this community service is to improve the knowledge and skills of the community in handling first aid for burns in Ledug Village, Kembaran District, BanyumasRegency. The method of community service is by lecture and demonstration methods. Participans who attended and participated in the activity were 40 people. The activity was carried out in the yard of the Alwakafiyah Mushola RW 05 Ledug Village, Purwokerto on Tuesday, July 9, 2024. The media used were powerpoint, leaflets, and videos. Results of community service characteristics of participants based on age, the largest is 56-75 years old with 25 participants, participants based on education are elementary school with 25 participants, while the largest participant based on occupation are housewives with 35 participants. Level of knowledge before education, 13 participants (32.5%), have sufficient knowledge. Meanwhile, after being given education, 31 participants (77,5%) are in the good category. Level of skills before given education and demonstration, all participants are unskilled, 40 participants (100%), meanwhile, after being given education and demonstration, 24 participants (50%), have skilled and 10 participants (40%) have less skilled.